Knowledge and Attitude about Multidrug-Resistant Tuberculosis among Healthcare Workers in Public Health Centres - Bony Wiem Lestari; Arto Yuwono Soeroto (Althea Medical Journal, 2016)
Background: Multidrug-resistant Tuberculosis (MDR-TB) is a significant public health problem and poses a threat to global tuberculosis (TB) control. In 2015, at least 504 new MDR-TB cases were identified in Indonesia. Treating MDR-TB patients is very challenging. It may take more than two years for MDR-TB treatment. Therefore, it is crucial healthcare workers (HCWs) are knowledgeable about MDR-TB. The aim of this study was to measure level of knowledge and attitude regarding MDR-TB among HCWs in public health centres.Methods: A cross-sectional study was conducted at 73 Public Health Centres in Bandung the capital of West Java Province from August until November 2015. The samples were 73 TB nurses and 32 laboratory staff. A self-administered questionnaire was given comprising 27 knowledge questions and 29 attitude questions. Correlation between knowledge and attitude scores was calculated by Pearson correlation test.Results: The majority of study participants were women (82.9%), married (92.4%), nursing staff (65.7%) with history of TB training (98.1%). Most of the participants were 40-59 years old (69.5%) with working experience in TB programme < 10 years (69.5%). Less than half (38.1%) of study participants had good knowledge. In terms of attitude, more than half (53.3%) of study participants had a positive attitude towards MDR-TB.Conclusions: The level of knowledge among HCWs about MDR-TB is still at an unacceptable level. Certain educational interventions aim to ensure prompt diagnosis, implement infection control and accurate treatment should be established among those HCWs. [AMJ.2016;3(4):509–13]DOI: 10.15850/amj.v3n4.932